Effect of Aggregate Fine Contents on Foamed Bitumen Stabilisation - Huan, Yue; Jitsangiam, Peerapong; Siripun, Komsun; Nikraz, Hamid (International Society for Asphalt Pavements (ISAP), 2012)
Increased popularity of foamed bitumen as a stabilising agent in recent years has resulted in a necessity for research into the material properties of foamed bitumen stabilised pavements, and the effects of varied design parameters on these properties. The objective of this project is to assess the effects of aggregate gradation in foamed bitumen mixes on material properties characteristics and mechanical performance. The focus was given into the fines particle percentage: that is, particles with a nominal diameter of 75µm or less, as it is recognised that this range of particle sizes has a significant effect on binding capabilities of foamed bitumen. The results were obtained by comparing a number of samples of ranging from 0% to 25% fines at 5% increments, and with 0%, 2% and 4% foamed bitumen contents. Comparisons were drawn by testing typical material properties of unconfined compressive strength, indirect tensile strength and indirect tensile resilient modulus. Test results indicated that deficient productions were yielded and nubby bitumen was easily to be observed with a lower amount of fines content. However, the higher fines content was detrimental to the mechanical strength which was mainly relied on the interlock between coarse particles.